Achieving food safety, the improvement of small-scale slaughterhouses through policy engagement - Chotinun, S.; Rojanasthien, S.; Unger, Fred; Suwan, M. (Veterinary Public Health Centre for Asia Pacific, 2013)
Food safety concerns are important to consumers and a focus of the Thai government. Applying food safety standards is often challenging for poultry production especially in rural area. Previous studies indicated that poultry meat and meat products were highly contaminated with food-borne pathogens including Salmonella and Campylobacter with poultry slaughterhouses as a major source for bacterial contamination. There is a lack of studies targeting effective interventions to improve poultry meat production and hygiene, particularly on policy that regulates such interventions. Using an EcoHealth approach, this study, aimed to develop feasible and cost effective guidelines for improvement of small-scale poultry slaughterhouses in Northern Thailand. Policy makers were involved from the early stage. Current laws and regulations for poultry slaughterhouses were reviewed, in depth interviews and focus group discussions with district and provincial authorities provided information on the enforcement of those regulations. Forty-one small-scale poultry slaughterhouses located in Chiang Mai were visited during July 2011-February 2013. Data on the current management and the need for improvement to address the current regulations were collected from slaughterhouse owners using structured questionnaires and checklists. The study revealed that despite the enforcement of slaughterhouse regulation since 1992 and GMP since 2006, none of the small-scale slaughterhouses in this study are able to meet the regulations and obtain license. The slaughterhouse owners reflected that current regulations and GMP are not feasible for small-scale slaughterhouses. Improper hygienic management was commonly practiced. The guideline for improving the slaughterhouse is developed and currently being implemented and evaluated through outcome mapping in selected slaughterhouses. Results of this study were discussed in a policy meeting with policy-level officers and will be reflected in a policy brief. Feedback from those discussions will be presented.